2015
DOI: 10.1089/fpd.2014.1801
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of Cauliflower, Broccoli, and Okara Byproducts Against Foodborne Bacteria

Abstract: The antimicrobial potential of cauliflower, broccoli, and okara byproducts was assessed against Gram-positive and Gram-negative bacteria. Salmonella enterica serovar Typhimurium, Escherichia coli O157:H7, Bacillus cereus, and Listeria monocytogenes serovar 4b growth behavior was assessed under exposure to 5% vegetable byproducts added to the reference medium, buffered peptone water (0.1% [wt/vol]), at 37°C. Although the byproducts were not effective against L. monocytogenes, they were bactericidal against Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…It has been reported that the lifespan of C. elegans is related with genetic and environmental factors, such as temperature, food availability and composition (Blumenthal and Steward, 1997;Uno and Nishida, 2016). According to Sanz-Puig et al (2015a) and Vieira (2013), cauliflower by-product infusion provides bioactive compounds such as polyphenols. It has been found that polyphenols contained in hydrophilic extracts of Brassica species are responsible for 80-95% of their total antioxidant capacity (Kurilich et al, 2002;Xianli et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the lifespan of C. elegans is related with genetic and environmental factors, such as temperature, food availability and composition (Blumenthal and Steward, 1997;Uno and Nishida, 2016). According to Sanz-Puig et al (2015a) and Vieira (2013), cauliflower by-product infusion provides bioactive compounds such as polyphenols. It has been found that polyphenols contained in hydrophilic extracts of Brassica species are responsible for 80-95% of their total antioxidant capacity (Kurilich et al, 2002;Xianli et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some natural antimicrobials by-products from plants (essential oils and plant extracts) have demonstrated their effectiveness against Salmonella Typhimurium in vitro (Sanz-Puig et al, 2015a;Mohamed et al, 2016). It has also been found that many vegetables in the Cruciferae family have antimicrobial properties against several microorganisms of clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…The next step was to evaluate virulence shifts in S. Typhimurium resulting from repetitive exposure to cauliflower by-product infusion. Cauliflower byproduct infusion contained bioactive compounds, as a ascorbic acid, carotenoids, flavonoids and, mainly, polyphenols such as galic acid, quercetin or rutin (Sanz-Puig et al, 2015;Vieira, 2013). To accomplish this goal, C. elegans were fed with S. Typhimurium exposed once and three times to cauliflower by-product infusion during their entire lifespan, and subsequently compared with C. elegans fed with untreated S. Typhimurium (control group).…”
Section: S Typhimurium With Cauliflower By-product Infusionmentioning
confidence: 99%
“…Many factors can affect bacterial survival on fruits and vegetables at the preharvest stage, including UV exposure (47,62), temperature (25), and produce surface drying (62). It is also known that produce may contain essential oils, antioxidants, and antimicrobial components that have an impact on microorganisms (59). Such compounds are naturally present in broccoli, and they may explain the low E. coli prevalence observed in this study.…”
Section: Resultsmentioning
confidence: 74%